Keluarga si Mamat - Lat Dato' 1951- (MPH Group Publishing, 2016)
Kampung Boy is a favorite of millions of readers in Southeast Asia. With masterful economy worthy of Charles Schultz, Lat recounts the life of Mat, a Muslim boy growing up in rural Malaysia in the 1950s: his adventures and mischief-making, fishing trips, religious study, and work on his family's rubber plantation. Meanwhile, the traditional way of life in his village (or kampung) is steadily disappearing, with tin mines and factory jobs gradually replacing family farms and rubber small-holders. When Mat himself leaves for boarding school, he can only hope that his familiar kampung will still be there when he returns. Kampung Boy is hilarious and affectionate, with brilliant, super-expressive artwork thatopens a window into a world that has now nearly vanished.